2000
DOI: 10.1097/00003246-200001000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transport of the extremely ill patient: The mobile intensive care unit

Abstract: When a mobile intensive care unit is properly staffed and equipped and patient stabilization is performed before transfer, severely ill patients with respiratory failure can be transferred safely. For patients with respiratory failure, there may be a survival advantage in transfer to regional centers of expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 33 publications
4
47
1
3
Order By: Relevance
“…ST segment elevation myocardial infarction (STEMI), acute trauma requiring surgery, stroke), taking the time to optimise the patient's haemodynamic and respiratory status prior to transport has been found to improve morbidity and mortality. [16,17] In fact, one study showed a shorter hospital stay when paramedics stayed longer at the referring facility stabilising the patient. [18] In order to achieve patient stability, a variety of procedures and medications must be administered by the CCT team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ST segment elevation myocardial infarction (STEMI), acute trauma requiring surgery, stroke), taking the time to optimise the patient's haemodynamic and respiratory status prior to transport has been found to improve morbidity and mortality. [16,17] In fact, one study showed a shorter hospital stay when paramedics stayed longer at the referring facility stabilising the patient. [18] In order to achieve patient stability, a variety of procedures and medications must be administered by the CCT team.…”
Section: Discussionmentioning
confidence: 99%
“…[18] In order to achieve patient stability, a variety of procedures and medications must be administered by the CCT team. [16][17][18] The current paramedic scope of practice locally is mainly focused on emergency, rather than critical care. [4] Often paramedics are left to initiate or monitor medication infusions that are outside of their scope of practice (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of transporting critically ill patients to tertiary hospitals for advanced care has been well described. gebremichael et al 17 showed that critically ill patients can be transported safely and that transfer of patients with severe respiratory failure to tertiary care centers has a survival advantage. Ridley and Carter 18 reported that patients have a predictable physiological response to transfer, independent of the severity of the underlying disease; that is, patients with higher critical illness scores did not have worse outcomes during transport.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a nurse accompanied the patient in all four studies that reported transport team composition. Interfacility transport is increasingly becoming the jurisdiction of highly trained and specialized transport personnel [35][36][37][38], with at least one paediatric study demonstrating significantly decreased morbidity associated with the use of such teams [36]. Professional guidelines have suggested that transport of unstable critically ill adults should be accompanied by either a physician or a nurse, preferably with additional training and experience in transport medicine [22].…”
Section: Discussionmentioning
confidence: 99%